2009
DOI: 10.1089/ten.tea.2008.0593
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Hyaluronan Oligomers and Transforming Growth Factor-Beta1 Factors for Elastic Matrix Regeneration by Aneurysmal Rat Aortic Smooth Muscle Cells

Abstract: The progression of aortic aneurysms (AAs) is typically associated with an activated smooth muscle cell (SMC) phenotype, diminished density of mature medial elastic fibers, and an elevated presence of matrix-degrading enzymes, which ultimately leads to vessel rupture. Currently, no surgical or nonsurgical methods are available to regress aneurysms via regeneration of new elastic matrices, particularly because of inherently poor elastin synthesis by adult vascular cells and absence of tools to stimulate the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…In EaRASMC cultures, unlike in healthy RASMC cultures, low dose combinations of HA-o ( < 20 mg/mL) and TGF-b ( < 10 ng/mL) had no effect on tropoelastin production; this agrees well with our prior findings that diseased SMCs require higher doses of these factors for elastogenic stimulation. 16 Also, as seen in our trend curves (Fig. 5C), the dependence of tropoelastin synthesis on HA-o dose is enhanced at higher doses of concurrently delivered TGF-b.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In EaRASMC cultures, unlike in healthy RASMC cultures, low dose combinations of HA-o ( < 20 mg/mL) and TGF-b ( < 10 ng/mL) had no effect on tropoelastin production; this agrees well with our prior findings that diseased SMCs require higher doses of these factors for elastogenic stimulation. 16 Also, as seen in our trend curves (Fig. 5C), the dependence of tropoelastin synthesis on HA-o dose is enhanced at higher doses of concurrently delivered TGF-b.…”
Section: Discussionsupporting
confidence: 77%
“…28 More recently, we demonstrated that SMCs isolated from rat aortal expansions created by peri-adventitial caustic injury, which resemble early stage AAAs, (a) continue to exhibit an abnormal, activated phenotype when passaged in vitro culture, (b) are much more elastogenically challenged relative to healthy, passagematched RASMCs, and can (c) be elastogenically stimulated in vitro with HA-o and TGF-b factors. 16 The relevance of the present study lies in the fact that AAAs are often only diagnosed at advanced stages of development, when matrix deterioration is severe. Since cell behavior is influenced by their microenvironment, there is a need for evidence that SMCs from such severely afflicted tissues can also respond favorably to elastogenic stimulation, and if so, if the effective doses of elastogenic factors differ significantly from that we ascertained useful with healthy RASMCs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…6 The present results suggest that (a) interaction with the collagenous ECM alters SMC behavior compared to 2D cultures, and (b) such collagen-SMC interaction de-sensitizes the cells to TGFb1 and HA-o, attested to by a significant decrease in cell number only at the highest provided doses. It is also apparent from our results that similar to our recently published observations in 2D cultures, TGF-b1 effects dominate with a biphasic dose-dependent proliferative response to TGF-b1 at both HA-o doses.…”
mentioning
confidence: 52%
“…5 Of potential benefit to overcoming the poor elastogenicity of adult vascular cells, our laboratory previously determined the synergistic benefits of hyaluronan oligomer (HA-o) and transforming growth factor-beta1 (TGF-b1) to elastin precursor synthesis, elastic matrix deposition, and fiber formation by cultured adult rat and human SMCs. 6,7 We also showed that TGF-b1 increases expression levels of mRNA for tropoelastin, and that of the matrix crosslinking enzyme, lysyl oxidase (LOX), while suppressing the activity of matrix degrading matrix metalloproteinases (MMPs). 7,8 Negatively charged HA is also thought to coacervate tropoelastin molecules for more efficient localized crosslinking and organization of these precursors into mature fibers, much like the role of glycosaminoglycans (GAGs) in a developing aorta.…”
Section: Introductionmentioning
confidence: 98%